Spatially resolved observation of crystal-face-dependent catalysis by single turnover counting - Roeffaers, Maarten B. J.; Sels, Bert F.; Uji-i, Hiroshi; De Schryver, Frans C.; Jacobs, Pierre A.; De Vos, Dirk E.; Hofkens, Johan (Nature, 2006)
Catalytic processes on surfaces have long been studied by probing model reactions on single-crystal metal surfaces under high vacuum conditions. Yet the vast majority of industrial heterogeneous catalysis occurs at ambient or elevated pressures using complex materials with crystal faces, edges and defects differing in their catalytic activity. Clearly, if new or improved catalysts are to be rationally designed, we require quantitative correlations between surface features and catalytic activity—ideally obtained under realistic reaction conditions 1 , 2 , 3 . Transmission electron microscopy 4 , 5 , 6 and scanning tunnelling microscopy 7 , 8 have allowed in situ characterization of catalyst surfaces with atomic resolution, but are limited by the need for low-pressure conditions and conductive surfaces, respectively. Sum frequency generation spectroscopy can identify vibrations of adsorbed reactants and products in both gaseous and condensed phases 9 , but so far lacks sensitivity down to the single molecule level. Here we adapt real-time monitoring of the chemical transformation of individual organic molecules by fluorescence microscopy 10 , 11 , 12 to monitor reactions catalysed by crystals of a layered double hydroxide immersed in reagent solution. By using a wide field microscope, we are able to map the spatial distribution of catalytic activity over the entire crystal by counting single turnover events. We find that ester hydrolysis proceeds on the lateral { } crystal faces, while transesterification occurs on the entire outer crystal surface. Because the method operates at ambient temperature and pressure and in a condensed phase, it can be applied to the growing number of liquid-phase industrial organic transformations to localize catalytic activity on and in inorganic solids. An exciting opportunity is the use of probe molecules with different size and functionality, which should provide insight into shape-selective or structure-sensitive catalysis 13 , 14 , 15 and thus help with the rational design of new or more productive heterogeneous catalysts.